Foreign investment and competitive development in Latin America and the Caribbean - Vera-Vassallo, Alejandro C. (1996)
Focuses on the importance of foreign investment for the countries of Latin America and the Caribbean in the first half of the 1990s, against the background of the new regional and world circumstances.